The burden of Invasive Aspergillosis in patients with haematological malignancy: A meta-analysis and systematic review. Issue 6 (June 2018) - van de Peppel, R.J.; Visser, L.G.; Dekkers, O.M.; de Boer, M.G.J.
Highlights: Invasive Aspergillosis is a frequently occurring complication of treatment for leukaemia. Even when antifungal prophylaxis is used, the risk of IA remains substantial. The case fatality rate of IA has improved over the years but is still estimated at 29%. Summary: Introduction: Successful treatment of haematological malignancies is frequently complicated by Invasive Aspergillosis (IA), a life-threatening fungal infection that occurs in at least 10% of haemato-oncological patients. Case fatality rates (CFR) may fluctuate over time, depending on host pathogen interactions as well as on treatment and quality of patient care. We conducted a systematic review and metaanalysis of current – i.e. 2008-revised EORTC-MSG criteria era – incidence and case fatality rates (CFR) of IA in patients with haematological malignancy. Methods: A systematic search according to PRISMA guidelines was performed to identify all literature reporting populations with a haematological malignancy and the incidence of IA, defined according to the EORTC/MSG 2008 criteria. Pooled cumulative incidences and CFR within 100 days were estimated using a random effects model for predefined patient populations and stratified by use of prophylaxis. Results: The systematic literature search yielded 1285 publications of which n = 49 met the inclusion criteria. Overall, 16.815 patients were involved of which 1056 (6.3%) developed IA. IA risk ranged from 4% (during remission-induction, with prophylaxis) to 11% (during remission-induction, without prophylaxis). Antifungal prophylaxis was associated with a lower rate of IA, especially in the pre-HSCT population. The pooled CFR within 100 days was 29% (95% CI: 20–38%). Discussion: This study confirms that IA is a relevant threat in the treatment of haematological cancer despite the universal use of antifungal prophylaxis. These outcomes inform scientists and other stakeholders about the current burden of IA and may be used to direct, implement and improve antifungal stewardship programs.